Early integration of palliative care in hospitals: A systematic review on methods, barriers, and outcome. Issue 6 (13th March 2014) - Dalgaard, Karen Marie; Bergenholtz, Heidi; Nielsen, Marianne Espenhain; Timm, Helle
Abstract: Objective: According to the World Health Organization (WHO), palliative care (PC) should be available to everyone suffering from life-threatening diseases and should be started early on in the illness trajectory. However, PC is often initiated much later and is restricted to cancer patients. There is a need for more knowledge about how early PC can be implemented in clinical practice. The purpose of our study was to document the best evidence on methods for early identification (EI) of palliative trajectories in cancer, chronic heart failure (CHF), and chronic obstructive pulmonary disease (COPD) populations, and to identify preconditions for early integration of general PC in hospitals and outcomes for patients and relatives. Method: A comprehensive systematic review of methods, preconditions, and outcomes was conducted via an electronic literature search of publications between 2002 and September 2012. A final sample of 44 papers was reviewed in detail. Results: Our study identified disease-specific and general methods for EI of patients who might benefit from PC. Prognostication of end-stage disease based on (holistic) clinical judgment, prognostic factors, and/or care needs are the most frequently recommended methods. A number of interacting disease-, staff-, user-, and organization-specific barriers need to be overcome in order to implement early integration of PC in clinical practice. Early integration of PC may lead to better symptom management, prolonged survival, and better quality of life. Significance of Results: No methods can be recommended for routine clinical practice without further validation. There is an urgent need to develop and evaluate methods based on the holistic assessment of symptoms or needs. The barriers to early integration of PC are most extensive with regard to CHF and COPD. Professional training and education are recommended to facilitate early implementation of PC. The evidence about outcome is sparse and mostly relates to cancer populations receiving specialized PC.